New constraints on the 12CO(2-1)/(1-0) line ratio across nearby disc galaxies - Brok, Jakob den; Chatzigiannakis, D.; Bigiel, F.; Puschnig, J.; Barnes, A. T.; Leroy, A. K.; Jiménez-Donaire, M. J.; Usero, A.; Schinnerer, Eva; Rosolowsky, E.; Faesi, C. M.; Grasha, K.; et al. (Monthly notices of the Royal Astronomical Society, 2021)
Both the CO(2-1) and CO(1-0) lines are used to trace the mass of molecular gas in galaxies. Translating the molecular gas mass estimates between studies using different lines requires a good understanding of the behaviour of the CO(2-1)-to-CO(1-0) ratio, R21. We compare new, high-quality CO(1-0) data from the IRAM 30-m EMIR MultiLine Probe of the ISM Regulating Galaxy Evolution survey to the latest available CO(2-1) maps from HERA CO-Line Extragalactic Survey, Physics at High Angular resolution in Nearby Galaxies-ALMA, and a new IRAM 30-m M51 Large Program. This allows us to measure R21 across the full star-forming disc of nine nearby, massive, star-forming spiral galaxies at 27 arcsec (∼1-2 kpc) resolution. We find an average R21 = 0.64 ± 0.09 when we take the luminosity-weighted mean of all individual galaxies. This result is consistent with the mean ratio for disc galaxies that we derive from single-pointing measurements in the literature, $R_{\rm 21, lit}~=~0.59^{+0.18}_{-0.09}$. The ratio shows weak radial variations compared to the point-to-point scatter in the data. In six out of nine targets, the central enhancement in R21 with respect to the galaxy-wide mean is of order of ${\sim}10{-}20{{\ \rm per\ cent}}$. We estimate an azimuthal scatter of ∼20 per cent in R21 at fixed galactocentric radius but this measurement is limited by our comparatively coarse resolution of 1.5 kpc. We find mild correlations between R21 and carbon monoxide (CO) brightness temperature, infrared (IR) intensity, 70-160 µm ratio, and IR-to-CO ratio. All correlations indicate that R21 increases with gas surface density, star formation rate surface density, and the interstellar radiation field.
Gesehen am 25.08.2021
Im Titel ist die Zahl 12 hochgestellt